PENDAMPINGAN PENGELOLAAN KEUANGAN DESA GUNA MENINGKATKAN AKUNTABILITAS DI DESA WERDHI BHUWANA - Kadek Wiwin Dwi Wismayanti; Putu Eka Purnamaningsih; Ni Wayan Ari Sudiartini (UNHI Press, 2021)
The efforts of the central government in maximizing services, development, and community at the village level so that villages can be more independent in managing their government and can maximize the various natural resources they have in order to improve the quality of life and welfare of rural communities with the passing of Law Number 6 of 2014. The enactment of the Law Number 6 of 2014 to date to Permendagri Number 113 of 2014 concerning village financial management. The implementation of village financial management is mandated to accelerate the improvement of the quality of accountability for state finances. Having a clear accountability by the government to the community is very important in realizing good governance. Measuring the performance of government officials is one of the components in the public performance accountability system that can also be used in assessing the performance of village financial management. The amount of authority given to the village government in regulating its own governance means the great responsibility that the village government has in carrying out its duties. The allocation of village funds can also raise concerns because not all village financial management apparatus have adequate capacities. For example, the ability to spend and produce accountable village financial reports. Through trainings and massive educational outreach, it can improve the competence of village officials in managing village finances. The method used in this service is in the form of socialization and education related to the procedures for preparing good and correct financial reports to the village financial management apparatus, through several methods such as lectures, tutorials, discussions, and mentoring. In addition, the existence of socialization and education activities on village financial management not only increases the capacity of village apartments but also increases community understanding regarding the management of village funds. Thus, this dedication is expected to be able to improve the capacity and competence of village financial management officials and village officials in Werdhi Bhuwana Village, so that they can better compile village financial management reports.